Superior Antireflection Coating for a Silicon Cell with a Micronanohybrid Structure - Hsi-Chien Liu; Gou-Jen Wang (International Journal of Photoenergy)
The object of this paper is to develop a high antireflection silicon solar cell. A novel two-stage metal-assisted etching (MAE) method is proposed for the fabrication of an antireflective layer of a micronanohybrid structure array. The processing time for the etching on an N-type high-resistance (NH) silicon wafer can be controlled to around 5 min. The resulting micronanohybrid structure array can achieve an average reflectivity of 1.21% for a light spectrum of 200–1000 nm. A P-N junction on the fabricated micronanohybrid structure array is formed using a low-cost liquid diffusion source. A high antireflection silicon solar cell with an average efficiency of 13.1% can be achieved. Compared with a conventional pyramid structure solar cell, the shorted circuit current of the proposed solar cell is increased by 73%. The major advantage of the two-stage MAE process is that a high antireflective silicon substrate can be fabricated cost-effectively in a relatively short time. The proposed method is feasible for the mass production of low-cost solar cells.